Manajemen Pembiayaan berbasis Agribisnis di Pesantren Miftahul Ulum Bangsalsari dan Pesantren At- Tanwir Ledokombo Jember - Fawaidi, Badrun (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
ABSTRACT This study aims to analyze and find: 1) How pesantren explore sources of agribusiness-based financing. 2) allocation and distribution of agribusiness-based pesantren financing. 3) Financing planning for agribusiness-based pesantren at Mifatahul Ulum Islamic Boarding School, Bangsalsari and At-Tanwir Islamic Boarding School Ledokombo Kab. Jember. 4) Implementation of agribusiness-based Islamic boarding school financing at Mifatahul Ulum Islamic Boarding School Bangsalsari and At-Tanwir Islamic Boarding School Ledokombo Kab. Jember. 5) Evaluation of agribusiness-based pesantren financing at Mifatahul Ulum Islamic Boarding School, Bangsalsari and At-Tanwir Ledokombo Islamic Boarding School, Jember Regency. These focuses were investigated using the approach to the theory of Financing Management proposed by Thomas H. Jones and several other relevant theories. This study uses a qualitative research approach through a phenomenological model with a multi-site design. Data collection techniques were carried out by non-participant observation, interviews, and documentation. Furthermore, the data were analyzed using several steps, namely: data collection, data condensation, data presentation, and drawing conclusions or verification. The findings of this study are: 1) The source of financing for Islamic boarding schools is done by managing coffee fields. 2) Allocation and distribution are used to finance the needs of pesantren based on unit cost and based on the type and priority of needs in accordance with eight national education standards. 3) Islamic boarding school financing planning is carried out in a transparent manner, proportional to the components that are related to the pesantren, such as alumni, students, and the community. 4) The implementation of pesantren financing is carried out by building trust between pesantren and pesantren stakeholders. Instilling the value of struggle and caring for pesantren stakeholders by empowering and involving them in every activity. Dividing work according to ability and regulated by written procedures. 5) Evaluation of pesantren financing is carried out seriously for the success of the activities planned with stakeholders and the community. Evaluation is done creatively and anticipating everything that could happen in the future. Evaluation is carried out on a regular basis involving pesantren stakeholders. Evaluation is carried out in a family atmosphere. The results of the evaluation are carried out as soon as possible with follow-up activities. Keywords: Financing Management, Islamic Boarding School, Agribusiness